DIFFERENCES IN PLATELET COUNTS USING BLOOD SAMPLES WITH K3EDTA AND 3.2% SODIUM CITRATE ANTICOAGULANTS IN DENGUE FEVER PATIENTS - Ni Luh Nova Dilisca Dwi Putri Prasetya; Anak Agung Istri Ari Trisnaningrum; Putu Ayu Parwati (PT. Jurnal Center Indonesia Publisher, 2025)
Dengue Hemorrhagic Fever (DHF) is a viral infection marked by a significant decrease in platelet count. Accurate platelet count testing is crucial for diagnosing and monitoring DHF patients. The pre-analytical phase is a critical stage in laboratory testing, where errors can significantly impact test outcomes. Anticoagulants, such as K3EDTA and 3.2% sodium citrate, are commonly used in routine hematology tests to prevent blood clotting by binding calcium ions and inhibiting clotting factor activation. This study aimed to evaluate the difference in platelet counts between blood samples collected with K3EDTA and 3.2% sodium citrate anticoagulants in DHF patients. An analytical observational study with a cross-sectional design was conducted involving 50 purposively sampled DHF patients. Statistical analysis yielded a p-value of 0.615 (p > 0.05), indicating no significant difference in platelet counts between the two anticoagulants. It can be concluded that the use of K3EDTA and 3.2% sodium citrate does not significantly affect platelet count results in DHF patients. Future studies are recommended to involve larger sample sizes and consider microscopic examination methods, such as peripheral blood smears, to assess platelet aggregation visually.